Analysing the Adoption of Intelligent Agent Technology in Food Supply Chain Management: An Empirical Evidence. Issue 4 (December 2022) - Mukherjee, Subhodeep; Chittipaka, Venkataiah
This article aims to identify and analyse the factors that impact the adoption of intelligent agent technology (IAT) in the food supply chain (FSC). The research was conducted based on 329 respondents from various hotels and the theoretical framework adopted in this study, that is, technological, organizational and environmental (TOE) framework. The findings indicated that multiple factors in TOE contribute significantly to the adoption of IAT. We have validated the proposed framework by structural equation modelling utilizing AMOS 22.0. This research offers a new and vital paradigm for adopting this innovation in the FSC, thereby increasing the overall efficiency of a hotel. The proposed TOE framework has identified several factors like relative advantage, reliability, complexity, cost, innovation adoption, top management support, skilled employees, IT awareness, environmental uncertainty, competitive pressure, information intensity and supplier's pressure, which helps in the adoption process of IAT in the FSC. It also provides a foundation for future research and significant insights to adopt this new technology in the hotel industry.